A Note on Passepartout Problems - Arantza Estevez-Fernandez; Peter Borm; Herbert Hamers (Tinbergen Institute, 2010)
This note provides a methodological contribution to the allocation of joint revenues obtained from passepartouts. In a passepartout system a group of service providers offers a passepartout that allows its owners the use of specified services for an unlimited number of times during a fixed period of time. The corresponding allocation problem is then how to share the total joint revenues of the passepartout system adequately among the service providers. Arguments are provided to model a passepartout problem within the framework of bankruptcy and context-specific properties are considered in order to select an appropriate allocation rule.
Keywords: D70; 330; Passepartout problem; bankruptcy problem; allocation rule; Insolvenz; Allokation; Neue politische Ökonomie